La psicología en Costa Rica: Encrucijada en el nuevo milenio - Cordero Cordero, Teresita; Salas Calvo, José Manuel (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The saturation o the psychology labor market is leading psychology in Costa Rica toward a severe crisis. Neoliberal politics also allow and promote different ways o employment compared to those o past decades. This situation implies several challenges for the formation and exercise of psychological practice in Costa Rica within a rather dark panorama. We offer a critical view to sustain this thesis. In addition we raise questions that encourage dialogue and reflection from different vantage points, within and outside our country. We aim to motivate alliances between the Central American countries to learn of psychologists´ employment conditions and training so that we can jointly answer these questions.